Pengaruh Financial Technology Terhadap Inklusi Keuangan Umkm Binaan Bank Indonesia Lhokseumawe - Yunita, Nur Afni; Wahdayani, Wahdayani; Rais, Rany Gesta Putri; Yusra, Muhammad (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2024)
This study aims to analyze the effect of financial technology on financial inclusion UMKM Binaan Bank Indonesia Lhokseumawe. This quantitative study using primary data sources and secondary data. The data collection technique in this research uses a questionnaire. Data analysis uses multiple linear regression analysis using SPSS. The samples are 48 UMKM Binaan Bank Indonesia Lhokseumawe taken using a sampling jenuh  technique. The result using a partial test reveal that Cashless Payment type fintech has a positive effect on financial inclusion UMKM Binaan Bank Indonesia Lhokseumawe. Market Aggregator type fintech has a positive effect on financial inclusion UMKM Binaan Bank Indonesia Lhokseumawe. Risk and Investment Management type fintech has a negative effect on financial inclusion UMKM Binaan Bank Indonesia Lhokseumawe.